Wnt-expressing rat embryonic fibroblasts suppress Apo2L/TRAIL-induced apoptosis of human leukemia cells - Doubravská, Lenka; Šímová, Šárka; Čermák, Lukáš; Valenta, Tomáš; Kořínek, Vladimír; Anděra, Ladislav (Apoptosis, 2008)
Wnt signaling enhances cell proliferation and the maintenance of hematopoietic cells. In contrast, cytotoxic ligand Apo2L/TRAIL induces the apoptosis of various transformed cells. We observed that co-culture of human pre-B leukemia cells KM3 and REH with Wnt1- or Wnt3a-producing rat embryonic fibroblasts efficiently suppressed Apo2L/TRAIL-induced apoptosis of the lymphoid cells. This suppression occurs at the early stages of the Apo2L/TRAIL apoptotic cascade and, interestingly, the activation of the Wnt pathway alone in human leukemia cells is not sufficient for their full anti-apoptotic protection. We hypothesize that a stimulus emanating specifically from Wnt1- or Wnt3a-expressing rat fibroblasts is responsible for the observed resistance to Apo2L/TRAIL. This anti-apoptotic signaling was significantly hampered by the inhibition of the MEK1/ERK1/2 or NFkappaB pathways in KM3 and REH cells. Our results imply that paracrine Wnt-related signals could be important for the survival of pre-B cell-derived malignancies.
Keywords: kokultivační techniky; financování organizované; Animals; beta-katenin; Cycloheximide; apoptóza; Rats; daktinomycin; Cell Line, Tumor; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Apoptosis; proteiny Wnt; lidé; Dactinomycin; signální transdukce; protein TRAIL; Signal Transduction; Financing, Organized; cykloheximid; Wnt1 Protein; Wnt Proteins; Apoptosis Regulatory Proteins; proteiny regulující apoptózu; Coculture Techniques; krysa rodu Rattus; zvířata; pre-B-buněčná leukemie; TNF-Related Apoptosis-Inducing Ligand; beta Catenin; protein Wnt1; nádorové buněčné linie; Humans